2017
DOI: 10.1097/md.0000000000006362
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of surgery alone versus surgery following preoperative chemoradiotherapy for early T3 rectal cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
2
8
0
2
Order By: Relevance
“…Post‐nCRT EMVI positivity also indicates reduced survival . The depth of invasion of a malignant tumor beyond the outer border of the muscularis propria (pT3) is considered an important prognostic factor in rectal carcinoma, with a pT3 depth above 5 mm representing an adverse prognostic factor for DFS (hazard ratio [HR] 2.13, 95% confidence interval [CI] 1.16–3.89) . Studies have also shown that the pathologic T category (ypT) and N stage (ypN) after nCRT are relevant independent prognostic factors for survival .…”
mentioning
confidence: 99%
“…Post‐nCRT EMVI positivity also indicates reduced survival . The depth of invasion of a malignant tumor beyond the outer border of the muscularis propria (pT3) is considered an important prognostic factor in rectal carcinoma, with a pT3 depth above 5 mm representing an adverse prognostic factor for DFS (hazard ratio [HR] 2.13, 95% confidence interval [CI] 1.16–3.89) . Studies have also shown that the pathologic T category (ypT) and N stage (ypN) after nCRT are relevant independent prognostic factors for survival .…”
mentioning
confidence: 99%
“…Therefore, the results with improved OS with PRCT in recto-sigmoid colon cancers must be interpreted with caution. In another study, early T3 rectal cancer patients who were either treated with surgery alone versus PRCT showed that 5-year local recurrence rate was 2% for both groups, and 5-year DFS were not statistically different (87% in surgery alone versus 88% in PRCT group) ( 33 ). Recently, a meta-analysis on total neoadjuvant therapy (TNT) addressed that TNT increases pathological down staging compared with surgery and adjuvant CRT ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Es konnte gezeigt werden, dass sich Lokalrezidivrate und rezidivfreies Überleben bei frühen T3-Stadien (pT3ab) und fehlender Infiltration der mesorektalen Fasziebasierend auf der MRT-Einschätzungmit und ohne neoadjuvante Radio-Chemotherapie nicht unterscheiden [28]. Diese Ergebnisse haben noch nicht zu einer Änderung der Therapieempfehlungen in der aktuellen Version der Leitlinie geführt [8].…”
Section: Bedeutung Der Mesorektalen Faszieunclassified